LEGAL PROTECTION OF CANCELLED PROSPECTIVE HAJJ AND UMRAH CONTRIBUTORS DURING COVID-19 PANDEMIC: THE BASIS OF LAW NO. 8/2019 CONCERNING THE ORGANIZATION OF HAJJ AND UMRAH - Kurniawan, Nicko Diaz; Nuroini, Indi (Srawung: Journal of Social Sciences and Humanities, 2022)
The impact of Covid-19 which caused hajj and umrah trips were having problem, therefore the government has limited these worship activities to held during this pandemic. There are two objectives of this research, such as to find out the accuracy of the government's policy regarding the cancellation of Hajj and Umrah departures during the Covid-19 pandemic and to analyze the legal protection stipulated under Law No. 8/2019 regarding the cancellation of the departure of prospective pilgrims. The method used in this research is a logical examination method combined with a standardized exploration strategy (juridical regularizing) and a conceptual approach. The existence of this pandemic caused the government to issue a new regulation, that is a decision through KMA No. 494/2020 and KMA No. 660/2021 concerning cancellation of Hajj departures. The policy contains security, safety, and health with the aim that pilgrims are not exposed to the Covid-19 virus. The type of government protection for prospective pilgrims, such as ensuring security, comfort, and funds for pilgrims who cancel their Hajj or Umrah.